Pesantren Ramah Perempuan Dan Anak Di Indonesia: (Studi Pada Pondok Pesantren Bahrul Ulum Tambakberas, Jombang, Jawa Timur dan Boarding School Education Mu’allimat, Muhammadiyah, Yogyakarta) - Fauzi Hamzah, Akhmad; Fajri, Barlian (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Abstract As an Islamic educational institution, pesantren have a strategic role in creating a child- and women-friendly environment. This research captures the efforts of Pesantren Bahrul Ulum Tambakberas Jombang and Muhammadiyah Boarding School Yogyakarta (PPMBS) in realizing child- and women-friendly pesantren. Using a descriptive-qualitative method, this study reveals three main findings. First, these two pesantren develop an integrated Islamic values-based model with preventive, educative, and curative approaches. Pesantren Bahrul Ulum focuses on internal synergy through continuous training and integrative activities, while PPMBS utilizes technology such as CCTV as well as external cooperation with counseling institutions and community organizations. Second, the optimization of internal resources in both pesantren includes ongoing training for educators, campaigns on empathy values, and seminars to raise awareness of the importance of an inclusive pesantren environment. Utilization of external resources is carried out through collaboration with the government, community, and related institutions to create a safe and friendly environment for women and children. Third, the internal challenges faced include the lack of awareness of some santri on the importance of child- and women-friendly values, as well as the negative influence of social media and the environment outside the pesantren. Solutions in both pesantren involve educational approaches, strengthening communication, and cooperation with external parties. This research shows that an Islamic value-based approach, integration of local culture, and external cooperation can be an effective model in creating child- and women-friendly pesantren in the contemporary era. Keywords: Pesantren, Women-Friendly, Children-Friendly, Indonesia.